Peningkatan Keaktifan, Motivasi, Hasil Belajar IPS melalui Model Pembelajaran Numbered Head Together - E. Dwi Kurniyanti; Sunarti Sunarti (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to 1) increase the activeness of students in social studies learning through the NHT (Numbered Head Together) learning model in class VI students of SD Negeri Kenteng, Banyuurip District, Purworejo Regency for the 2021/2022 academic year. 2) increase the motivation of students in social studies learning through the NHT (Numbered Head Together) learning model in class VI students of SD Negeri Kenteng, Banyuurip District, Purworejo Regency for the 2021/2022 academic year. 3) improve social studies learning outcomes through the NHT (Numbered Head Together) learning model for class VI students at SD Negeri Kenteng, Banyuurip District, Purworejo Regency for the 2021/2022 academic year. The type of research is classroom action research. The research subjects were students of class VI SD Negeri Kenteng totaling 28 students, 15 male and 13 female. The research was conducted in 3 cycles with 2 meetings in each cycle. Data collection techniques using observation and written tests. The data analysis technique used descriptive statistical analysis. The results show that 1) the NHT (Numbered Head Together) learning model can increase the activity of students in class VI SD Negeri Kenteng for the academic year 2021/2022 with a success indicator of 70% of students meeting the medium category, namely pre-cycle by 32.14%, cycle I was 42.86%, the second cycle was 60.71%, and the third cycle was 75%. 2) The use of the NHT (Numbered Head Together) learning model increases the motivation of students in class VI SD Negeri Kenteng for the 2021/2022 academic year with a success indicator of 70% of students meeting the minimum medium category, namely pre-cycle of 17.86%, cycle I of 28,57%, the second cycle of 53.57%, and the third cycle of 71.43%. 3) The use of the NHT (Numbered Head Together) learning model can improve student learning outcomes in class VI SD Negeri Kenteng for the 2021/2022 academic year with the research success category of 70% of students fulfilling the KKM for social studies lesson content (75), namely the pre-cycle of 39 .29%, the first cycle of 53.57%, the second cycle of 60.71%, and the third cycle of 71.43%.